Electro-dewatering pretreatment of sludge to improve the bio-drying process. Issue 47 (29th August 2019) - Sha, Li; Yu, Xiaoyan; Liu, Xingxin; Yan, Xiaotong; Duan, Jingxiao; Li, Yingte; Zhang, Shuting
Abstract : The feasibility of electro-dewatering (EDW) as a pretreatment of the subsequent bio-drying process was investigated in this study. Abstract : In this study, the feasibility of electro-dewatering (EDW) as a pretreatment of the subsequent bio-drying process (EB process) was investigated from the point of view of the influence of EDW on the microbial biodegradability of sludge. The results showed that suitable EDW pretreatment was beneficial for microbial growth in the sludge cake, and in the subsequent bio-drying process it increased the metabolic activity of microorganisms. However, electric field strength impacted microbial activity and soluble chemical oxygen demand (SCOD) of the sludge. As the applied electric field strength increased from 20 to 60 V cm −1, the microbial activity of sludge decreased gradually but SCOD of sludge increased. The specific oxygen uptake rate (SOUR) at electric field strength of 20 V cm −1 was 8.7% higher than that of raw sludge. EDW pretreatment accelerated the drying rate of bio-drying process, and the final water content of sludge (44%) was 6.3% lower than that of non-pretreated sludge. It was observed that in the bio-drying process with an EDW pretreatment, the first peak temperature of the sludge pile was 58.7 °C at 36 h and the second peak temperature was 48.7 °C at 56 h, whereas that of the non-pretreated sludge was only 46.5 °C at 42 h and 40.3 °C at 62 h, respectively. The EDW sludge incorporating straw as a bulking agent showed promising results during bio-drying. In addition, EDW pretreatment of sludge to improve the bio-drying process showed lower energy consumption and cost.